Lactate mediated metabolic crosstalk between cancer and immune cells and its therapeutic implications - Mortazavi Farsani, Seyedeh Sahar; Verma, Vivek (Frontiers in Oncology, 2023)
Metabolism is central to energy generation and cell signaling in all life forms. Cancer cells rely heavily on glucose metabolism wherein glucose is primarily converted to lactate even in adequate oxygen conditions, a process famously known as "the Warburg effect." In addition to cancer cells, Warburg effect was found to be operational in other cell types, including actively proliferating immune cells. According to current dogma, pyruvate is the end product of glycolysis that is converted into lactate in normal cells, particularly under hypoxic conditions. However, several recent observations suggest that the final product of glycolysis may be lactate, which is produced irrespective of oxygen concentrations. Traditionally, glucose-derived lactate can have three fates: it can be used as a fuel in the TCA cycle or lipid synthesis; it can be converted back into pyruvate in the cytosol that feeds into the mitochondrial TCA; or, at very high concentrations, accumulated lactate in the cytosol may be released from cells that act as an oncometabolite. In immune cells as well, glucose-derived lactate seems to play a major role in metabolism and cell signaling. However, immune cells are much more sensitive to lactate concentrations, as higher lactate levels have been found to inhibit immune cell function. Thus, tumor cell-derived lactate may serve as a major player in deciding the response and resistance to immune cell-directed therapies. In the current review, we will provide a comprehensive overview of the glycolytic process in eukaryotic cells with a special focus on the fate of pyruvate and lactate in tumor and immune cells. We will also review the evidence supporting the idea that lactate, not pyruvate, is the end product of glycolysis. In addition, we will discuss the impact of glucose-lactate-mediated cross-talk between tumor and immune cells on the therapeutic outcomes after immunotherapy.